Investigating the application of the Principles for Responsible Management Education to resort mini-clubs. Issue 2 (July 2020) - Seraphin, Hugues; Thanh, Tan Vo
Abstract: Sustainability is an important issue facing the tourism and hospitality industry in the twenty-first century. Children are the tourists of the future. However, little is known about how to educate them to be responsible tourists, in other words, citizens who would be respectful of the destinations visited. The present research attempts to answer this gap. To this end, this research suggests an innovative education-based approach, taking children as a target and resort mini-clubs as a tool. To the question: Where are the children in tourism research? This study has provided evidence that they are still disempowered, and it is even more the case when it comes to sustainability. That said, with the implementation of Principles for Responsible Management Education (PRME) through edutainment activities in mini-clubs' programmes of activities, they could play a more significant role. Practically, resort mini-clubs' managers need to adopt an ambidextrous management approach which would help them not only to enhance the experience of visitors, but also to potentially increase their revenue. Highlights: Children are the tourists of the future. The programme of activities for resort mini-clubs applying PRME is empowering children in the tourism industry. The hospitality sector could contribute to the Gap Frame at Economy and Society levels. This new approach for the design of programmes for resort mini-clubs could be part of the Corporate Social Responsibility of resorts.